Hubungan Industrial Pancasila Dalam Undang-Undang Cipta Kerja - Kususiyanah, Anjar (Invest Journal of Sharia & Economic Law, 2021)
Pancasila industrial relation is a relationship between the government, employers, and workers based on the Pancasila ideology. It is appropriate that the formation of regulations regarding employment are also based on Pancasila and the 1945 Constitution. The Law describes the legal ideals of Indonesian workers, which are in line with the national development Pancasila ideology system so that all elements, both workers and entrepreneurs, feel welfare as aspired by all Indonesian people. Since the workforce is the most critical factor in the national development sector, it is appropriate that the regulations governing Manpower are always discussed and in the spotlight of policymakers, academics, and Indonesian workers. The human resources sector is included in one of the discussions in the work creation law, which President Joko Widodo initiated. However, there is a degradation in the value of welfare for workers in Indonesia. There are several shifts in the content of Manpower, including regarding Foreign Workers (TKA), Time Work Agreements. Certain (PKWT), outsourcing (outsourcing), wages. This study examines the value of Pancasila industrial relations in the Employment Copyright Act with a qualitative descriptive method to understand a Pancasila industrial relations concept in the Work Copyright Act, researchers using material analysis techniques (content analysis) and library research. The purpose of this research is to be used as a reference for policymakers as a material for judicial review to realize the nation's welfare. The results of this study state that the concept of Pancasila industrial relations is not yet fully attached to the Employment Copyright Act. Therefore, there must be a joint effort to rebuild industrial relations based on Pancasila so that industrial relations in Indonesia can run smoothly, relatively, and based on deliberation for consensus to build a better Indonesia in the international community's eyes.